Glucose Oxidation to Pyruvate Is Not Essential for Brucella suis Biovar 5 Virulence in the Mouse Model - Lázaro-Antón, Leticia; de Miguel, María Jesús; Barbier, Thibault; Conde-Álvarez, Raquel; Muñoz, Pilar M.; Letesson, Jean Jacques; Iriarte, Maite; Moriyón, Ignacio; Zúñiga-Ripa, Amaia (Frontiers in Microbiology, 2021)
Brucella species cause brucellosis, a worldwide extended zoonosis. The brucellae are related to free-living and plant-associated α2-Proteobacteria and, since they multiply within host cells, their metabolism probably reflects this adaptation. To investigate this, we used the rodent-associated Brucella suis biovar 5, which in contrast to the ruminant-associated Brucella abortus and Brucella melitensis and other B. suis biovars, is fast-growing and conserves the ancestral Entner-Doudoroff pathway (EDP) present in the plant-associated relatives. We constructed mutants in Edd (glucose-6-phosphate dehydratase; first EDP step), PpdK (pyruvate phosphate dikinase; phosphoenolpyruvate ⇌ pyruvate), and Pyk (pyruvate kinase; phosphoenolpyruvate → pyruvate). In a chemically defined medium with glucose as the only C source, the Edd mutant showed reduced growth rates and the triple Edd-PpdK-Pyk mutant did not grow. Moreover, the triple mutant was also unable to grow on ribose or xylose. Therefore, B. suis biovar 5 sugar catabolism proceeds through both the Pentose Phosphate shunt and EDP, and EDP absence and exclusive use of the shunt could explain at least in part the comparatively reduced growth rates of B. melitensis and B. abortus. The triple Edd-PpdK-Pyk mutant was not attenuated in mice. Thus, although an anabolic use is likely, this suggests that hexose/pentose catabolism to pyruvate is not essential for B. suis biovar 5 multiplication within host cells, a hypothesis consistent with the lack of classical glycolysis in all Brucella species and of EDP in B. melitensis and B. abortus. These results and those of previous works suggest that within cells, the brucellae use mostly 3 and 4 C substrates fed into anaplerotic pathways and only a limited supply of 5 and 6 C sugars, thus favoring the EDP loss observed in some species.